COMPLEX EFFECT OF MODIFICATION ON THE PROPERTIES OF Γ-ALLOY BASED ON TITANIUM ALUMINIDE (Modern Problems of Metallurgy, 2025)
Titanium aluminide-based alloys are a promising class of materials, the range of effective use of which is 600-800°C. The advantages of γ-alloys are low density, high structural stability, and heat resistance. The main forming technology for producing parts based on aluminides is casting, which forms a coarse-grained microstructure of the ingot with low values of strength and ductility characteristics. One of the practically feasible ways to improve the properties of γ-alloys is modification. The mechanism of action of modifying elements is adsorption on the surface of grains, which contributes to a change in the surface activity of crystals and the rate of diffusion and leads to a change in the shape and size of crystals. The effect of modifying elements Y, Re, and B on the properties of an alloy based on titanium aluminide of the Ti-28Al-7Nb-2Mo system was investigated using the full-factorial experimental design method. In accordance with the experimental planning matrix using a laboratory vacuum arc furnace with a copper water-cooled crystallizer, ingots of various compositions were melted. A study of the chemical composition, metallographic analysis of the macro- and microstructure, determination of mechanical properties, and analysis of the fracture surface of the samples after testing were carried out. The mechanical properties of the alloy – ultimate strength and ductility – were chosen as optimization parameters. The obtained regression equations make it possible to calculate the chemical composition of the alloy in accordance with the required level of material properties of the aviation product. Also, by substituting the content of modifying elements into the equation, it is possible to predict the results of the mechanical properties of an alloy based on titanium aluminide of the Ti-28Al-7Nb-2Mo system. The optimal composition of the titanium aluminide-based alloy was determined, which provides the value of mechanical properties σв ≥800MPa and plasticity ≥1%.
Keywords: titanium aluminide; full-factor experiment; modifying elements; regression equations; optimization parameters; response function; mechanical properties.